The Empowered Integrated Health Posyandu’s Program: Improving Toddler Nutrition and Boosting Household Economy in Kutaliman, Kedungbanteng, Banyumas Regency: The Empowered Integrated Health Posyandu’s Program: Improving Toddler Nutrition and Boosting Household Economy in Kutaliman, Kedungbanteng, Banyumas Regency - Seskowati, Sus; Yohandoko, Setyo (Corespub, 2023)
The knowledge about the nutritional status of toddlers is very important for every parent because malnutrition can have an impact on a child's development. Malnutrition issues in toddlers can be caused by several factors including socio-economic conditions, maternal nutrition quality during pregnancy, infant health, and the level of nutrient intake during infancy. Specific measures in the field of nutrition are more focused on addressing the root causes of nutritional problems, such as dietary patterns and infectious diseases, and fall within the framework of health policies. The goal of community empowerment efforts is to improve the quality of life and social status of communities currently living in poverty so they can change their circumstances. One form of empowerment in improving nutrition is by harnessing the resources available in villages, such as agricultural products, plantations, livestock, and fisheries, which are then creatively processed by the local community to produce nutritious products and enhance household economic potential. In this endeavor, we identify that in nearly every region, future generations face serious threats related to the nutritional status of toddlers. Therefore, preventive measures starting at the household level are essential. Through the Empowered Integrated Health Posyandu’s program, the goal of improving toddler nutrition from the household level can be realized through community outreach, guidance, and active participation especially in Kutaliman, Kedungbanteng, Banyumas Regency.